Country report on multimedia and Internet for children and youth in Taiwan - Ho, Hong-Fa (The Turkish Journal of Pediatrics, 1999)
The actions of Taiwan government for promoting information education have being carried out since 1996. The main goal is to educate students of primary school and high school about the basic information knowledge and the internet. The actual actions will be described. There are many kind of multimedia CD titles In Taiwan market right now. The major types of multimedia CD titles will be discussed. And the difficulties of developing materials of CD titles will be discussed.